Antimicrobial susceptibility surveillance of obligate anaerobic bacteria in the Kinki area - Shimura, Satoshi; Watari, Hideo; Komatsu, Masaru; Kuchibiro, Tomokazu; Fukuda, Saori; Nishio, Hisaaki; Kita, Machiko; Kida, Kaneyuki; Oohama, Masanobu; Toda, Hirofumi; Nishio, Motoi; Nishi, Isao; et al. (Journal of infection and chemotherapy : official journal of the Japan Society of Chemotherapy, 2019)
Obligate anaerobes exist as resident flora in various sites in humans, but they are also emphasized as endogenous causative microorganism of infections. We performed surveillance to understand the trend of drug susceptibility in obligate anaerobic bacteria in the Kinki area of Japan. In the experiment, we used 156 obligate anaerobe isolates collected from 13 institutions that participated in the Study of Bacterial Resistance Kinki Region of Japan. MALDI Biotyper was used to identify the collected strains, and among the 156 test strains, those that could be identified with an accuracy of Score Value 2.0 or more included 6 genera, 30 species, and 144 strains (Bacteroides spp. 77 strains, Parabacteroides sp. 2 strains, Prevotella spp. 29 strains, Fusobacterium spp. 14 strains, Porphyromonas spp. 2 strains, and Clostridioides difficile 20 strains), and they were assigned as subject strains for drug susceptibility testing. The drug susceptibility test was carried out by broth microdilution method using Kyokuto Opt Panel MP ANA (Kyokuto Pharmaceutical Industrial Co., Ltd., Tokyo, Japan) and judged according to CLSI criteria. As a result, Bacteroides and Parabacteroides species showed good sensitivities to tazobactam-piperacillin, imipenem, metronidazole and chloramphenicol, and low sensitivities to ampicillin, cefoperazone and vancomycin. Prevotella species showed good sensitivities to sulbactam-ampicillin, tazobactam-piperacillin, cefmetazole, imipenem, doripenem and metronidazole. Susceptibility rates to other drugs were slightly different depending on the bacterial species. Both Fusobacterium spp. and Porphyromonas spp. showed high sensitivities to many drugs. C. difficile was highly sensitive to vancomycin and metronidazole, having MIC90s of 0.5 μg/mL and ≤2 μg/mL, respectively.